KONTRIBUSI SEKTOR BASIS DAN NON-BASIS TERHADAP PERTUMBUHAN EKONOMI KABUPATEN ASAHAN: ANALISIS LOCATION QUOTIENT - Heni Widiya; Al Bina; Putri Pamularsih (Smart Education, 2026)
Abstract : Asahan Regency is one of the districts in North Sumatra Province that has quite diverse economic potential, ranging from the agricultural sector, plantations, processing industry, trade, to services. The economic structure of Asahan Regency is inseparable from the role of leading sectors that are able to generate surpluses and encourage economic activities in other regions. This study aims to analyze the influence of the base sector and the non-base sector on economic growth in Asahan Regency during the period 2016–2024. This method uses a quantitative approach with secondary data obtained from the Central Statistics Agency. The determination of the base and non-base sectors was carried out using the Location Quotient method, while the analysis of its influence on economic growth used the Ordinary Least Square method. The results of show that there are four base sectors in Asahan Regency, namely the agriculture, forestry and fisheries sectors; the processing industry; large and retail trade; and other services. The value of the determination coefficient of 73.5% of the variation in economic growth can be explained by the base sector and the non-base sector, while the rest is influenced by other factors outside the research model. Keywords: Base Sector, Non-Base Sector, Economic Growth, Location Quotient Abstrak : Kabupaten Asahan merupakan salah satu kabupaten di Provinsi Sumatera Utara yang memiliki potensi ekonomi cukup beragam, mulai dari sektor pertanian, perkebunan, industri pengolahan, perdagangan, hingga jasa. Struktur perekonomian Kabupaten Asahan tidak terlepas dari peran sektor-sektor unggulan yang mampu menghasilkan surplus dan mendorong aktivitas ekonomi wilayah lain. Penelitian ini bertujuan untuk menganalisis pengaruh sektor basis dan sektor non basis terhadap pertumbuhan ekonomi di Kabupaten Asahan selama periode 2016–2024. Metode ini menggunakan pendekatan kuantitatif dengan data sekunder yang diperoleh dari Badan Pusat Statistik. Penentuan sektor basis dan non basis dilakukan menggunakan metode Location Quotient, sedangkan analisis pengaruhnya terhadap pertumbuhan ekonomi menggunakan metode Ordinary Least Square. Hasil menunjukkan bahwa terdapat empat sektor basis di Kabupaten Asahan, yaitu sektor pertanian, kehutanan dan perikanan; industri pengolahan; perdagangan besar dan eceran; serta jasa lainnya. Nilai koefisien determinasi 73,5% variasi pertumbuhan ekonomi dapat dijelaskan oleh sektor basis dan sektor non basis, sedangkan sisanya dipengaruhi oleh faktor lain di luar model penelitian. Kata Kunci : Sektor Basis, Sektor Non Basis, Pertumbuhan Ekonomi, Location Quotient